Ambient Influences on Municipal Net Assets: Evidence from Panel Data - Davies, Stephen P.; Johnson, Laurence E.; Lowensohn, Suzanne (Contemporary Accounting Research, 2017)
Abstract Governments’ net assets balances are viewed as a measure of fiscal health and have been linked to municipal credit ratings. This study explores the extent to which ambient socioeconomic factors are captured in aggregated restricted and unrestricted net assets balances (termed “liquid net assets”) to understand why such balances are relevant to credit analysts and others. We model liquid net assets balances using observable nonaccounting factors (e.g., unemployment rates) to learn whether they reflect such influences. We use panel data for fiscal years 2007–2011 so our results comprehend effects of recent economic fluctuations. We find that liquid net assets balances impound a rich array of influences, bearing a positive association with the mayor‐council form of government, community wealth, the incidence of property crimes, and increases in governments’ business‐type net assets. Liquid net assets balances bear a negative association with liabilities for postemployment benefits, unemployment, and violent crime. The results indicate that net assets balances capture noteworthy debt burden, administrative, and socioeconomic influences and, as such, have meaning beyond their basic accounting interpretation.